Formalizing Local Intersectoral Practices: A Case Study of an Initiative Targeting Language Development. - Di Sante, Mélissa; Bilodeau, Angèle; Chabot, Catherine; Potvin, Louise (Canadian Journal of Speech-Language Pathology & Audiology, 2023)
Intersectoral action is a potential avenue for increasing the availability of and access to language-oriented resources in local communities. Although this strategy has been recommended for reducing social inequalities between children of different communities, the effective practices that underlie intersectoral action (i.e., what intersectoral networks do to achieve change) are rarely discussed in the field of speech-language pathology. The objective of this case study was to document the process of a local intersectoral initiative aimed at promoting the language development of preschool-aged Bengali children living in Montréal. Documentary sources and interviews with key informants were used to reconstruct the chronological story and to identify critical events that were crucial to the progression of the intersectoral process. Critical events were interpreted in the light of three essential functions that lead intersectoral networks to produce change: (a) network setup and governance, (b) representing and influencing, and (c) aligning essential actors and resources. The analysis revealed that the network produced outcomes related to all three functions to achieve their goal. The importance of network-building practices with people from different activity sectors, institutional commitments to build bridges between institutional and community settings, and engaging in participatory approaches are highlighted in the analysis. By identifying effective practices of local intersectoral action, this study can guide speech-language pathologists and actors in early childhood who wish to engage in intersectoral work to act on resources for language development in their local areas.